CORELATION OF GLOBAL LONGITUDINAL STRAIN (GLS) – LEFT VENTRICLE AND SOLUBLE SUPRESSION OF TUMORGENICITY 2 (sST2) IN ACUTE HEART FAILURE WITH SYSTOLIC DYSFUNCTION - Herlina Yulidia; Muhammad Aminuddin; Budi S Pikir (The Indonesian Heart Association, 2018)
Background : Assessment of left ventricular function in patients with acute heart failure is important for prognostication, determination of treatment plan, for decisions related to expensive device therapies and for assessing response to treatment. Echocardiography is the